Tracing the Price of the Discourse Power in Media Diplomacy - June Cahyaningtyas (The Indonesian Journal of Communication Studies, 2008)
Media is one among many tools used in diplomatic practice. Apart from being mechanical, the media cannot be isolated from the social and cultural situations from which the message produced and understood, the political economic interests for which the message created, and the networks of actors by which the contours of the discourse took relevance. Discourse power of the media is warrant by the providence of the media as public space. The nature of discourse power can be seen through its mobility, interactivity and fluidity. The power of the discourse may promote peace as much as conflict, and be utilized for preserving mass compliance as much as steering movements of global resistance.